Auditing financial assets in accordance with international auditing standards (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:                The research aims to identify the general framework of financial assets and audit procedures in accordance with international auditing standards, and to prepare an audit program to audit financial assets in accordance with international auditing standards, as it provides important practical assistance to auditors when addressing the subject of evaluation and other considerations related to financial assets, and for the auditor to obtain reasonable assurance. Concerning whether the financial statements as a whole are free from fundamental errors, whether resulting from fraud or error, the research has reached a set of conclusions, the most important of which are: The audit programs approved and issued by the Federal Office of Financial Supervision and the accounting control and auditing companies do not meet the audit requirements under The new accounting treatments indicated in accordance with the International Financial Reporting Standards with regard to financial assets. The research also reached the most important recommendations: the necessity of adopting the proposed audit program that was designed by the researcher in the Federal Office of Financial Supervision and the audit and control companies, which shows how to audit the accounts that fall within The scope of the requirements of international standards, which includes clear audit procedures for each item that falls within the scope of international standards, to help the external auditor rely on it when auditing financial assets and expected credit losses.